2019
DOI: 10.1186/s12936-019-2953-1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of natural killer cells to the immune response against Plasmodium

Abstract: Natural killer (NK) cells are important innate effector cells that are well described in their ability to kill virally-infected cells and tumors. However, there is increasing appreciation for the role of NK cells in the control of other pathogens, including intracellular parasites such as Plasmodium, the cause of malaria. NK cells may be beneficial during the early phase of Plasmodium infection—prior to the activation and expansion of antigen-specific T cells—through cooperation with myeloid cells to produce i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 96 publications
3
37
0
2
Order By: Relevance
“…To determine which immune cells to study, we measured LILRB1 expression in peripheral white blood cells by antibody staining and flow cytometry, and found that, while LILRB1 is widely distributed, it is most prevalent in CD4 + T cells and NK cells ( Extended Data Figures 6 ). Of these, NK cells are most relevant in the context of malaria blood stage infection as they have recently been shown to interact with infected erythrocytes through antibody- dependent cell-mediated cytotoxicity (ADCC) 19 , 20 .…”
mentioning
confidence: 99%
“…To determine which immune cells to study, we measured LILRB1 expression in peripheral white blood cells by antibody staining and flow cytometry, and found that, while LILRB1 is widely distributed, it is most prevalent in CD4 + T cells and NK cells ( Extended Data Figures 6 ). Of these, NK cells are most relevant in the context of malaria blood stage infection as they have recently been shown to interact with infected erythrocytes through antibody- dependent cell-mediated cytotoxicity (ADCC) 19 , 20 .…”
mentioning
confidence: 99%
“…Natural killer (NK) cells play an important role in the innate immune response to malaria infection (10,11). NK cells are the first cells in peripheral blood to produce interferon gamma (IFN-γ) in response to P. falciparum infection (11), and they have also been shown to participate in adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the production of the regulatory cytokine IL-10 by NK cells prevents overt pathology and death from cerebral malaria in mouse models. 88 Fig. 2 NK receptors and responses to malaria.…”
Section: Introductionmentioning
confidence: 99%